2016
DOI: 10.1109/tit.2016.2555847
|View full text |Cite
|
Sign up to set email alerts
|

The ADMM Penalized Decoder for LDPC Codes

Abstract: Linear programming (LP) decoding for low-density parity-check (LDPC) codes proposed by Feldman et al. is shown to have theoretical guarantees in several regimes and empirically is not observed to suffer from an error floor. However at low signal-to-noise ratios (SNRs), LP decoding is observed to have worse error performance than belief propagation (BP) decoding. In this paper, we seek to improve LP decoding at low SNRs while still achieving good high SNR performance. We first present a new decoding framework o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 51 publications
2
100
0
Order By: Relevance
“…Before we go through the parameter optimization for the proposed decoder, we make a remark for the all-zeros assumption of the improved ADMM penalized decoder. Following the proof of the all-zeros assumption for the ADMM penalized decoder [7], we can see that the improved ADMM penalized decoder also satisfy Lemma 18 in [7]. Then similar arguments can be used to show that Lemma 19 and Lemma 16 in [7] also hold for the improved ADMM penalized decoder.…”
Section: A Improved Admm Penalized Decoder For Irregular Ldpc Codesmentioning
confidence: 72%
See 3 more Smart Citations
“…Before we go through the parameter optimization for the proposed decoder, we make a remark for the all-zeros assumption of the improved ADMM penalized decoder. Following the proof of the all-zeros assumption for the ADMM penalized decoder [7], we can see that the improved ADMM penalized decoder also satisfy Lemma 18 in [7]. Then similar arguments can be used to show that Lemma 19 and Lemma 16 in [7] also hold for the improved ADMM penalized decoder.…”
Section: A Improved Admm Penalized Decoder For Irregular Ldpc Codesmentioning
confidence: 72%
“…Following the proof of the all-zeros assumption for the ADMM penalized decoder [7], we can see that the improved ADMM penalized decoder also satisfy Lemma 18 in [7]. Then similar arguments can be used to show that Lemma 19 and Lemma 16 in [7] also hold for the improved ADMM penalized decoder. Therefore, the improved ADMM penalized decoder satisfies the all-zeros assumption.…”
Section: A Improved Admm Penalized Decoder For Irregular Ldpc Codesmentioning
confidence: 72%
See 2 more Smart Citations
“…Besides, it is observed that the ADMM-based LP decoder has worse error performance than the MP decoder at low SNR values [25]. To address this problem, Liu et al proposed a penalized ADMM decoder which adds a penalty term into the objective function of the LP formulation.…”
Section: : End Formentioning
confidence: 99%